Mobilitas dan Survival Penjual Mie Ayam dan Bakso di Kawasan Pinggiran Kota Surakarta - Agus Anggoro Sigit; Priyono Priyono; Martini Martini; Jajang Susatyo (UM Purwokerto Press, 2024)
This research examines the mobility and survival strategies of the informal sector in urban areas, particularly chicken noodle and meatball vendors, amidst the pandemic. The research method employed a survey with 158 respondents in the outskirts of Surakarta city. The results indicate that the high economic growth influences the consumption patterns of society and the growth of the informal sector, such as meatball and chicken noodle vendors. The Covid-19 pandemic imposes significant pressure on the informal sector, yet most vendors continue to operate with different strategies. The mobility of informal sector workers is not only from the surrounding areas of Surakarta but also from outside the province, driven by the attractiveness of the destination city, good accessibility, and adequate road conditions. Almost 27% of vendors stopped operating during the pandemic, but the majority persevered with adaptive strategies depending on their situation and creativity.